2022
DOI: 10.1021/acscatal.2c04837
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Co–Nx Active Sites of MOF-Templated Co@NC Catalysts via Au Doping for Boosting Oxidative Esterification of Alcohols

Abstract: The Co–N x active sites play a critical role over the Co@NC catalyst in the heterogeneous catalysis. However, the effective methods for the regulation of the content and electronic structure of Co–N x active sites to enhance the catalytic efficiency of heterogeneous catalysts are still insufficient. Herein, a nitrogen-doped porous carbon-encapsulated Au-doped Co nanoparticle catalysts with abundant and electron-rich Co–N x sites in the outer carbon layer was designed by a Au doping strategy through pyrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…In the initial step, it was observed that the presence of either base or acid led to a reduction in CAL conversion, emphasising the significance of Lewis acid-base sites for the reaction (Supplementary Table 4 , Entry 2 and 3). KSCN, a recognised poison reagent capable of deactivating single atomic or metal sites 46 , resulted in a substantial decrease in CAL conversion from 95.0% to 53.7% when 20 mg KSCN was added to the reaction (Supplementary Table 4 , Entry 4). In the subsequent step, both pyridine and KSCN reduced the conversion of COL, while the impact of boric acid was minimal (Supplementary Table 4 , Entry 6–8).…”
Section: Resultsmentioning
confidence: 99%
“…In the initial step, it was observed that the presence of either base or acid led to a reduction in CAL conversion, emphasising the significance of Lewis acid-base sites for the reaction (Supplementary Table 4 , Entry 2 and 3). KSCN, a recognised poison reagent capable of deactivating single atomic or metal sites 46 , resulted in a substantial decrease in CAL conversion from 95.0% to 53.7% when 20 mg KSCN was added to the reaction (Supplementary Table 4 , Entry 4). In the subsequent step, both pyridine and KSCN reduced the conversion of COL, while the impact of boric acid was minimal (Supplementary Table 4 , Entry 6–8).…”
Section: Resultsmentioning
confidence: 99%
“…Esters contribute to many fruits' characteristic aroma and flavor, also often used as solvents, plasticizers, and raw materials for perfumery. 3,4 Hence, esters are produced through different methods, including the esterification of acids and oxidative esterification of aldehydes and alcohols (Scheme 1). Traditionally, this conversion has involved the use of stoichiometric amounts of oxidizing agents like KMnO 4 , O 3 , TBHP, and H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous catalysts such as noble metal catalysts (i.e., Au [22][23][24], Pt [25], Pd [26], etc.) as well as transition metal catalysts (i.e., Co [27,28], etc.) have shown great potential in the oxidative esterification process due to their capability of converting O 2 molecules into highly active atomic O or other reactive oxygen species [29].…”
Section: Introductionmentioning
confidence: 99%